2013
DOI: 10.1038/ismej.2013.215
|View full text |Cite
|
Sign up to set email alerts
|

Host immune responses accelerate pathogen evolution

Abstract: Pathogens face a hostile and often novel environment when infecting a new host, and adaptation is likely to be an important determinant of the success in colonization and establishment. We hypothesized that resistant hosts will impose stronger selection on pathogens than susceptible hosts, which should accelerate pathogen evolution through selection biased toward effector genes. To test this hypothesis, we conducted an experimental evolution study on Xanthomonas citri subsp. citri (Xcc) in a susceptible plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Interestingly, we did not detect phytoplasma sequences in U.G.B., even though the origin was sympatric with the other plants included in the study, suggesting that the rootstocks may influence the ecology of the phytoplasma by becoming potential reservoirs of these cell-wall-less grape pathogens. An analysis of the microbial network interactions may help to clarify the host-pathogen interactions and provide new insights into the pathogen colonization process [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we did not detect phytoplasma sequences in U.G.B., even though the origin was sympatric with the other plants included in the study, suggesting that the rootstocks may influence the ecology of the phytoplasma by becoming potential reservoirs of these cell-wall-less grape pathogens. An analysis of the microbial network interactions may help to clarify the host-pathogen interactions and provide new insights into the pathogen colonization process [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous experimental evolution study conducted by our group demonstrated that adapted Xcc bacteria that caused reduced HR-like phenotype in Meiwa kumquat harbor point mutations in a xps type 2 secretion system (T2SS) gene and the T3SS effector coding genes xopE1/ avrXacE1 and pthA4 [34]. We hypothesized that these genes mediate kumquat immune responses to Xcc.…”
Section: The Immune Responses Of Meiwa Kumquat To Xcc Are Mediated Bymentioning
confidence: 99%
“…Positive selection is an important driving force for pathogens in adaptation process (Lieberman et al, 2011;Trivedi and Wang, 2013). Knowledge of the genes affected by positive selection across citrus canker-causing species can show which genes may be involved in citrus canker development and host specificity.…”
Section: Phylogenetic Analysis Of Citrus Canker-causing Xanthomonasmentioning
confidence: 99%